Relationship between 8th Grade Secondary School Students’ Reading Attitudes and Reading Comprehension Skills - M. Eyyüp SALLABAS (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Language has two dimensions and these are comprehension (reading and listening) andexpression (speaking and writing). Reading takes place within the comprehensiondimension and it is one of the most influential ways of communication. Attitude isindividual’s response tendency against any phenomenon or object around him. Duringthe process of education and training, students are expected to develop positiveattitudes towards reading effectiveness. In this study it is aimed to determine the effectof student gender in the process of reading comprehension and developing attitudetowards reading. According to the results of this study, it is determined that there is alow level correlation between students’ attitudes towards reading and readingcomprehension skills. Also it is determined that there is a moderate level correlationbetween students’ reading comprehension skills and academic achievement.Furthermore, there is a significant difference between the percentage point of students’reading comprehension and attitudes towards reading in fever of girls.